2021
DOI: 10.1080/02681102.2021.1976714
|View full text |Cite
|
Sign up to set email alerts
|

Mobile phone use for social inclusion: the case of internally displaced people in Nigeria

Abstract: Internally Displaced People (IDP) have received less attention in ICT4D research. This study examines how IDP in Africa use mobile phones to enhance their social inclusion. We employed Sen's Capability Approach as the theoretical lens and a qualitative case study as a methodology. Qualitative data obtained from 21 conflict-induced IDP in Nigeria suggests that mobile phones serve not only as a self-help commodity to overcome disconnection from their communities but also a means to enhance their individual and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 56 publications
0
7
0
1
Order By: Relevance
“…They recommend focusing on counselling to enable IDPs to communicate their socio-economic needs. Moreover, Dasuki and Effah (2021) found that while IDPs make personal efforts to participate in society, stringent government policies for acquiring civil documents continue to frustrate such efforts toward social inclusion. Jonah et al (2022) examined how Nigerian media excluded IDPs from media coverage on the impact of COVID-19.…”
Section: Internal Displacement and Justicementioning
confidence: 99%
“…They recommend focusing on counselling to enable IDPs to communicate their socio-economic needs. Moreover, Dasuki and Effah (2021) found that while IDPs make personal efforts to participate in society, stringent government policies for acquiring civil documents continue to frustrate such efforts toward social inclusion. Jonah et al (2022) examined how Nigerian media excluded IDPs from media coverage on the impact of COVID-19.…”
Section: Internal Displacement and Justicementioning
confidence: 99%
“…A oferta de ações que promovam o aumento do convívio social dos idosos é de suma importância, pois devido à perda de entes queridos, muitos idosos podem sozinhos em seu meio social. Além disso, mesmo estando em contato com outras pessoas, eles podem não ter o apoio emocional de que necessitam (Carmona et al, 2014;Dasuki & Effah, 2022).…”
Section: Fonte: Produção Dos Autores (2023)unclassified
“…All these difficulties negatively affect their physical and mental health and well-being and make them more vulnerable [6,9]. The use of information and communication technologies (ICTs) for health, called digital health or eHealth [10,11], could be a promising avenue to address the challenges faced by these forced migrant populations, including internally displaced persons, refugees, asylum seekers, and economic, political, or climate migrants [2,[12][13][14][15][16][17]. Indeed, digital health technologies could play an important role in preventing and promoting the health and well-being of forced migrant populations [18,19].…”
Section: Overviewmentioning
confidence: 99%
“…To address these major challenges, many initiatives aimed at promoting better health behaviors among forced migrant populations have been developed by different actors [13,37,40]. A comprehensive understanding of these interventions to support digital health literacy among forced migrant populations and their effectiveness is essential to enable policy makers to develop programs and interventions tailored to their needs.…”
Section: Overviewmentioning
confidence: 99%